A systematic review of the non-surgical treatment of Perthes' disease. (1st December 2020) - Galloway, Adam M.; van-Hille, Thomas; Perry, Daniel C.; Holton, Colin; Mason, Laura; Richards, Suzanne; Siddle, Heidi J.; Comer, Christine
Abstract : Aims: Perthes' disease is a condition leading to necrosis of the femoral head. It is most common in children aged four to nine years, affecting around one per 1, 200 children in the UK. Management typically includes non-surgical treatment options, such as physiotherapy with/without surgical intervention. However, there is significant variation in care with no consensus on the most effective treatment option. Methods: This systematic review aims to evaluate the effectiveness of non-surgical interventions for the treatment of Perthes' disease. Comparative studies (experimental or observational) of any non-surgical intervention compared directly with any alternative intervention (surgical, non-surgical or no intervention) were identified from: Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), EMcare, Allied and Complementary Medicine Database (AMED), and the Physiotherapy Evidence Database (PEDro). Data were extracted on interventions compared and methodological quality. For post-intervention primary outcome of radiological scores (Stulberg and/or Mose), event rates for poor scores were calculated with significance values. Secondary outcomes included functional measures, such as range of movement, and patient-reported outcomes such as health-related quality of life. Results: In all, 15 studies (1, 745 participants) were eligible for inclusion: eight prospective cohort studies, seven retrospective cohort studies, and no randomized controlled trials were identified. Non-surgical interventions largely focused on orthotic management (14/15 studies) and physical interventions such as muscle strengthening or stretching (5/15 studies). Most studies were of high/unknown risk of bias, and the range of patient outcomes was very limited, as was reporting of treatment protocols. Similar proportions of children achieving poor radiological outcomes were found for orthotic management and physical interventions, such as physiotherapy or weightbearing alteration, compared with surgical interventions or no intervention. Conclusion: Evidence from non-randomized studies found no robust evidence regarding the most effective non-surgical interventions for the treatment of children with Perthes' disease. Future research, employing randomized trial designs, and reporting a wider range of patient outcomes is urgently needed to inform clinical practice. Cite this article: Bone Jt Open 2020;1-12:720–730.